2009
DOI: 10.1007/s00395-009-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial inflammation and non-ischaemic heart failure: is there a role for C-reactive protein?

Abstract: Whereas C-reactive protein (CRP) is acknowledged as a cardiovascular risk marker, there is ongoing discussion about its role as a risk factor. Previous studies focused on the effects of CRP on ischaemic heart failure and atherosclerosis. In this study we investigated distribution of CRP, the Terminal Complement Complex (C5b-9) and macrophages (CD68) in the myocardium of patients suffering from non-ischaemic heart failure and their implication on clinical parameters. Endomyocardial biopsies were taken from 66 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 43 publications
3
30
1
1
Order By: Relevance
“…23, 24 In addition, pathological examination of endomyocardial biopsies in patients with dilated cardiomyopathy revealed that CRP is frequently present in the myocardium and co-localizes with complement and macrophages. 25 These findings suggest that CRP itself might play some role in the development of LV dysfunction.…”
Section: Mano Y Et Almentioning
confidence: 96%
“…23, 24 In addition, pathological examination of endomyocardial biopsies in patients with dilated cardiomyopathy revealed that CRP is frequently present in the myocardium and co-localizes with complement and macrophages. 25 These findings suggest that CRP itself might play some role in the development of LV dysfunction.…”
Section: Mano Y Et Almentioning
confidence: 96%
“…Among 20 patients with "idiopathic" arrhythmias (predominantly atrial fibrillation, but also ventricular extrasystoles and left bundle branch block) myocarditis was observed in 75%, viral genome -only in 15.8% what probably can explain relatively favorable course of myocarditis. In separate cases of atrial fibrillation myocarditis was diagnosed in 66%, viral genome has never been studied [8].…”
Section: Resultsmentioning
confidence: 98%
“…По некоторым данным [15], он не коррелирует с морфо-логическими признаками миокардита (включая опреде-ление самого С-реактивного белка в ткани) у больных с ДКМП. Нами получены данные о достаточно высокой специфичности основных маркеров воспаления, но еще большее значение имело выявление ряда иммунных по-казателей (АТ к ДНК и др.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…While many causal mechanisms such as abnormal heart valves, inherited cardiomyopathies, severe coronary artery or hypertensive heart disease are easily identified in clinical practice, the precise mechanisms that determine the progression of heart failure and ventricular remodelling are largely unknown. In recent years, there is growing evidence that autoimmunity and inflammatory mechanisms may contribute to disease progression in heart failure [3,5,8,15].…”
mentioning
confidence: 99%